Qira`at fi Syar’iyyah al-Tatbiqat al-Mu’asarah li Buyu’ al-Dayn - Abu Zaid, Abd al-`Azim (Jurnal Fiqh, 2006)
Debt is a wealth obligation upon another person as a result of a contract of exchange, a loan or damages made on the other`s wealth. It is also normally related to wealth that is associated with interest or riba which has its own specific governing rules. Both of these features of debt has attracted persistent emphasis among the Muslim jurists in explaining the law of debts including its sale. In fact, the illegality of sale of debt and its vast implications upon monetary transactions has made it as one of the most frequently discussed subject among the jurists who have put an emphasis on the laws govering the sale of debts to prevent people from an indulgement in riba. Unfortunately, there are some Islamic financial institutions which has freely adopted it and have developed many financial products that contains features of this non-permitted sale. The applications were justified by the view of some jurists who has allowed it, the detachment between debts, and modern adaptation of the sale of debt. This article attempts to discuss the harmlessness of these justifications and see whether they authorize the usage of sale of debt in the modern Islamic financial institutions or better for them to abandon it in order to maintain their Islamicity.